Pravalensi dan Faktor Risiko Penyakit Tidak Menular di Desa Tanjung Selamat - Farhatu Zahra Adhani; Fitri Annisa Nuryadi; Mhd Dirga Riandi Ritonga; Mia Afrianti Harahap; Zata Ismah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Non-communicable diseases (NCDs) are chronic diseases that are not transmitted through direct contact. The occurrence of an epidemiological transition in response to changes in several factors in Indonesia today and causing changes in the pattern of disease distribution from infectious diseases to non-communicable diseases (PTM). Hypertension is a type of chronic disease whose symptoms are an increase in blood pressure in the arterial walls. Diabetes mellitus is a type of disease that is not contagious and is included in the type of metabolic disorder, this disease is characterized by chronic hyperglycemia caused by abnormalities in insulin secretion, insulin action and or both. The research method used in this study is the observation method through questionnaires distributed to the Tanjung Selamat village community, totaling 210 people with an age range of 19-84 years. In this study, PBL students of UIN Sumut (UINSU) Medan observed the people of Tanjung Selamat, and identified the level and factors that influence the risk of diabetes and PTM hypertension in Tanjung Selamat village. Based on the results of the study, respondents who were diagnosed with hypertension were 57.1% while those who did not were 42.9%, then respondents who experienced hypertension mostly had an age range above 30 years with male sex, had a smoking habit, lacked physical activity. , and eat salty foods. From observation, based on history of diabetes mellitus, the most respondents who did not have a history of DM with a percentage of 55.7% and respondents who had a history of DM with a percentage of 44.3%. From the data, it was found that when respondents were still implementing eating patterns that triggered the risk of diabetes, namely consuming sweet foods and consuming sweet drinks, as well as other behavioral factors such as smoking and lack of physical activity. Keywords: Prevalence, Risk Factors, Diabetes Mellitus, Hypertension, PTM.